Contribution for an Urban Geomorphoheritage Assessment Method: Proposal from Three Geomorphosites in Rome (Italy) - Pica, Alessia; Luberti, Gian Marco; Vergari, Francesca; Fredi, Paola; Del Monte, Maurizio (Quaestiones Geographicae, 2017)
Urban geomorphology has important implications in spatial planning of human activities, and it also has a geotouristic potential due to the relationship between cultural and geomorphological heritage. Despite the introduction of the term Anthropocene to describe the deep influence that human activities have had in recent times on Earth evolution, urban geomorphological heritage studies are relatively rare and limited and urban geotourism development is recent. The analysis of the complex urban landscape often need the integration of multidisciplinary data. This study aims to propose the first urban geomorphoheritage assessment method, which originates after long-lasting previous geomorphological and geotouristic studies on Rome city centre, it depict rare examples of the geomorphological mapping of a metropolis and, at the same time, of an inventory of urban geomorphosites. The proposal is applied to geomorphosites in the Esquilino neighbourhood of Rome, whose analysis confirm the need for an ad hoc method for assessing urban geomorphosites, as already highlighted in the most recent literature on the topic. The urban geomorphoheritage assessment method is based on: (i) the urban geomorphological analysis by means of multitemporal and multidisciplinary data; (ii) the geomorphosite inventory; and (iii) the geomorphoheritage assessment and enhancement. One challenge is to assess invisible geomorphosites that are widespread in urban context. To this aim, we reworked the attributes describing the Value of a site for Geotourism in order to build up a specific methodology for the analysis of the urban geomorphological heritage.